Peran pemerintah dalam implementasi kebijakan lingkungan di Kabupaten Sidoarjo - Hanif Rachmad Fauzie (Universitas Airlangga, 2022)
The environment is one of the elements of life that should be maintained properly. Especially water, where everyone must need water as the most important source of life for all humanity in the world. The role of the government in controlling water pollution in the Porong River, Sidoarjo Regency is the focus of research in this journal. This research is very important because the Porong River is a river from the Brantas watershed that is highly protected by the Provincial Government. In addition, this study uses descriptive qualitative methods. This is because so that researchers can easily explain how the role of the district government in maintaining and managing the environment. By using green political theory, this research is intended to understand the application of green politics in the implementation of environmental policies. Environmental programs such as the Environmental Management Performance System are the mainstay of the Sidoarjo Regency Government in controlling its environment, this program is supported by the existence of an environmental budget from the Sidoarjo Regency DPRD according to the mandate of Law No. 32 of 2009. The idea of ​​green political assumptions should be a guideline in the making and implementation of Sidoarjo regency policy so that sustainable development can be realized without overriding environmental aspects.